Collagen from Atlantic cod (Gadus morhua) skins extracted using CO2 acidified water with potential application in healthcare - Sousa, Rita Alexandra Oliveira (2020)
The extraction of collagen from fish skins is being proposed as strategy for valorization of marine origin by-products, being a sustainable alternative to mammal collagen. The method commonly uses solutions of organic acids, but new methodologies are arising, aiming to improve process yields and/or the properties of the resulting products. In this work, skins removed from salt brine Atlantic cod (Gadus morhua) were used to extract collagen, using water acidified with CO2, obtaining an extraction yield of 13.8% (w/w). Acidified water extracted collagen (AWC) presented a total content of proline-like amino acids of 151/1000 residues, with a degree of hydroxylation of 38%, and its SDS-PAGE profile is compatible with type I collagen. Moreover, FTIR, CD and XRD results suggest the presence of preserved triple helix, having a denaturation temperature of 32.3Â Â°C as determined by micro-DSC. AWC exhibited a typical shear thinning behavior, interesting regarding their further processing, namely in jelly-like formulations. Additionally, the presence of AWC in MRC-5 human fibroblasts culture did not affect cell viability, demonstrating the non-cytotoxic behavior. Overall, the results support the efficiency of the proposed approach for collagen extraction and further enable the design of methodologies to address AWC use in biomedical or cosmetic context.